2017
DOI: 10.1126/science.aal3999
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling solar and stellar magnetic cycles with nonlinear dynamo simulations

Abstract: The magnetic fields of solar-type stars are observed to cycle over decadal periods-11 years in the case of the Sun. The fields originate in the turbulent convective layers of stars and have a complex dependency upon stellar rotation rate. We have performed a set of turbulent global simulations that exhibit magnetic cycles varying systematically with stellar rotation and luminosity. We find that the magnetic cycle period is inversely proportional to the Rossby number, which quantifies the influence of rotation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
102
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(116 citation statements)
references
References 42 publications
12
102
1
1
Order By: Relevance
“…The other, "inactive" branch, however, remains robust in these same studies, and more importantly this cycle branch covers the solar activity-Rossby parameter regime. Both Babcock-Leighton flux transport dynamos (Jouve et al 2010;) and recent global MHD simulations (Strugarek et al 2017(Strugarek et al , 2018) are unable to reproduce this observed cycle period trend (however see Hazra et al 2019, who find some correct trend in a pumping-dominated dynamo model). By necessity, our study included only targets with high-quality cycles, which are the same set of stars comprising the inactive branch.…”
Section: Conclusion and Discussionmentioning
confidence: 98%
“…The other, "inactive" branch, however, remains robust in these same studies, and more importantly this cycle branch covers the solar activity-Rossby parameter regime. Both Babcock-Leighton flux transport dynamos (Jouve et al 2010;) and recent global MHD simulations (Strugarek et al 2017(Strugarek et al , 2018) are unable to reproduce this observed cycle period trend (however see Hazra et al 2019, who find some correct trend in a pumping-dominated dynamo model). By necessity, our study included only targets with high-quality cycles, which are the same set of stars comprising the inactive branch.…”
Section: Conclusion and Discussionmentioning
confidence: 98%
“…6.3, we will discuss how in a classical α − ω dynamo (and in the equivalent flux transport Babcock-Leighton alternative) there exists a simple link between the Rossby number and the Dynamo number D, that can explain the observed positive linear scaling between rotation period and magnetic cycle period (e.g., Durney and Latour 1978;Noyes et al 1984b;Baliunas et al 1996;Tobias 1998;Montesinos et al 2001;Jouve et al 2010). We will also discuss a subset of recent simulations that show that the magnetic cycle length could also increase rather than decrease with shorter rotation period (Jouve et al 2010;Strugarek et al 2017). …”
Section: Main Sequence Solar-like Starsmentioning
confidence: 99%
“…The absence of a self-consistent and realistically thin tachocline in these models may explain why they have difficulty producing solar-like magnetic cycles (e.g., Browning et al 2006). Although some models do generate dipolar magnetic fields with regular reversals (e.g., Käpylä et al 2012;Passos & Charbonneau 2014;Strugarek et al 2017), they lack the smaller-scale features that characterise the solar dynamo, such as the coherent magnetic flux tubes that form sunspots and magnetic prominences, which are generally believed to originate in the tachocline (Parker 1955). The tachocline may also influence the dynamics of the convection zone in other ways.…”
mentioning
confidence: 99%